Estudo da Infecção pelo Vírus da Hepatite B (HBV) em Caminhoneiros de Rota Longa do Brasil: Soroepidemiologia e Genótipos - MATOS, Marcos André de (2008)
The aim of this study was to investigate the seroepidemiological and molecular profile of the hepatitis B virus (HBV) infection in long distance truck drivers in Brazil. From October 2005 to 2006, 641 individuals were interviewed on sociodemographic and risk factors, and blood samples were collected to test for HBV markers (HBsAg, anti- HBs and anti-HBc) by the enzyme linked immunosorbent assay (ELISA). HBsAg positive samples were submitted to HBV DNA detection by polymerase chain reaction (PCR) and genotyping by restriction fragment length polymorphism (RFLP) analysis. A global prevalence of HBV was 18.9% (95% CI: 15.9-22.2): 16 were HBsAg positive, 117 anti-HBc total and 69 anti-HBs. Thirty truck drivers were anti- HBs only, suggesting vaccination against hepatitis B. Length of profession above 20 years, time away from home more than 15 days and history of sexually transmitted diseases (STD) were independently associated to HBV positivity by multivariate analysis. Among HBsAg-positive truck drivers, one (6.2%) were HBeAg reactive, nine (56.25%) anti-HBe positive and the rest negative for both markers. HBV DNA was detected in nine samples of the HBsAg-positive individuals, being identified the genotype A (22.2%), D (55.6%) and F (22.2%). These findings ratify the high risk of hepatitis B infection in truck drivers, and highlight the importance of public health politics addressed to this group whom presents characteristics which may favour HBV acquiring and it dissemination.